The worst volcanic eruptions of all time - Garbe, Suzanne (Mankato, Minn. : Capstone Press, 2012)
"Describes the worst volcanoes in history, as well as formation, types, and disaster tips"--Provided by publisher.
IG840L
Keywords: Volcanoes